The role of Solute Carrier Family 7 Member 8 (SLC7A8) in adipogenesis in vitro and in a murine model of obesity - Ambele, Melvin (University of Pretoria, 2023)
Thesis (PhD (Medical Immunology))--University of Pretoria, 2023.